Recovery of proximal and distal arm weakness in the ipsilateral upper limb after stroke - Jung, Han Young; Yoon, Joon Shik; Park, Bong Soon (NeuroRehabilitation (Reading, Mass.), 2002)
Conservation of the ipsilateral upper limb function is important in stroke subjects with contralateral hemiplegia, because often it must serve as a compensatory tool for activities of daily livings (ADLs). However, the amount of functional loss and/or the recovery pattern of the ipsilateral upper limb are not well known. We plan to investigate how to measure the progress of the ipsilateral upper limb function after the onset of stroke. Once a week we used the Manual Function Test (MFT) to evaluate the ipsilateral upper limb weakness of 72 stroke subjects with contralateral hemiplegia until maximum recovery. Proximal and distal arm weaknesses in the ipsilateral upper limb were maximally recovered within one month following the onset of hemispheric stroke, but their weakness was not to be completely recovered. Also the amounts of their recoveries were different from each other. These results indicate that the ipsilateral upper limb weakness in stroke is not a temporary event and that motor function of the proximal and distal arm might be mediated by different neuronal circuits.